Stability of the two enveloped viruses NDV LaSota and YF-ZIKprM/E to support process development - Sven Göbel; Lennart Jacobtorweihe; Max-Leopold Rössig; Frauke Braatz; Fabien Perugi; Yvonne Genzel; Udo Reichl (PLoS ONE, 2026)
Building on the established use of enveloped viral vectors, like lentivirus and vesicular stomatitis virus, we investigated the stability of the oncolytic Newcastle disease virus LaSota strain and the chimeric construct of a Zika vaccine candidate YF ZIKprM/E. These vectors are currently being developed for the treatment of solid tumors, such as melanoma and glioblastoma, and for vaccine initiatives, respectively. Virus stability is a critical attribute during cell culture-based virus production and also relevant for downstream processing, storage of the produced material, final vaccine storage and shelf life. Therefore, temperature and pH stability were tested as important parameters during upstream processing and freeze-thaw cycles were tested in context of laboratory-analytics. In this study, both viruses exhibited strong stability of the infectious virus titer when subjected to repeated freeze-thaw cycles. However, exposure to temperatures above 22°C substantially reduced the infectious titers, indicating sensitivity to elevated temperatures. To improve viral stability during storage, we investigated the use of sucrose as a stabilizing excipient. While this did not result in significant improvements for YF-ZIKV, an extended half-life for NDV at room temperature was observed. The observed half-life values of upstream material from NDV of 2.6 h and 2.8 h for YF-ZIKV at 37°C demand consideration of changes to the process design, such as the implementation of a perfusion process to enable continuous, cooled virus harvesting.